2018
DOI: 10.1039/c7ra11116a
|View full text |Cite
|
Sign up to set email alerts
|

AS1411 aptamer conjugated gold nanoclusters as a targeted radiosensitizer for megavoltage radiation therapy of 4T1 breast cancer cells

Abstract: In the present study, AS1411 aptamer conjugated gold nanoclusters (GNCs) have been introduced as a targeted radiosensitizer for enhancing megavoltage radiation therapy efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
72
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(73 citation statements)
references
References 65 publications
1
72
0
Order By: Relevance
“…Various types of surface modication of metal NCs, such as aptamer, specic peptides, glucose, DNA, and folic acid have been developed for efficient delivery of the metal NCs to the target (e.g., cancerous tumors) for in vivo applications. [151][152][153][154][155][156] Further studies involving active targeting of metal NCs would be important for in vivo PDT applications.…”
Section: Discussionmentioning
confidence: 99%
“…Various types of surface modication of metal NCs, such as aptamer, specic peptides, glucose, DNA, and folic acid have been developed for efficient delivery of the metal NCs to the target (e.g., cancerous tumors) for in vivo applications. [151][152][153][154][155][156] Further studies involving active targeting of metal NCs would be important for in vivo PDT applications.…”
Section: Discussionmentioning
confidence: 99%
“…Combination of AS1411, GNPs and photodynamic therapy have also shown therapeutic effects in the treatment of Hela cells (39) . Another study has showed that the combination of megavoltage radiation and AS1411 aptamer conjugated gold nanoclusters as a radiosensitizer causes effective cancer cell death and a dose enhancement factor (DEF) of about 2.7 in clonogenic survival assay in 4T1 breast cancer cells (40) . These data consist with our nding on SERs variation in different culture; 1.35, 1.66, 1.96 for MCf-7, MDA-MB-231 and mammosphere derived cells, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…They have found that the synthesized nanoprobe produced strongly darkened T 2weighted (90% reduction of signal intensity) in 4T1 cells at 45 µg/mL concentration. Recently, Ghahremani et al in 2018 [85,86] introduced bovine serum albumin (BSA) capped gold nanoclusters targeted by AS1411 aptamer as a gold radiosensitizing (with a size of 10-15 nm) candidate for megavoltage radiotherapy and biomedical imaging of breast cancer cells (4T1) targeting agent.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%